Oxidative modification to LDL receptor-related protein 1 in hippocampus from subjects with Alzheimer disease: Implications for Aβ accumulation in AD brain - Owen, Joshua B.; Sultana, Rukhsana; Aluise, Christopher D.; Erickson, Michelle A.; Price, Tulin O.; Bu, Guojun; Banks, William A.; Butterfield, D. Allan (Free radical biology & medicine, 2010)
Alzheimer disease (AD) is a neurodegenerative disorder characterized histopathologically by the presence of senile plaques (SPs), neurofibrillary tangles, and synapse loss. The main component of SPs is amyloid-β peptide (Aβ), which has been associated with increased oxidative stress, leading to oxidative modification of proteins and consequently to neurotoxicity and neurodegeneration. Low-density lipoprotein receptor-related protein 1 (LRP1) is the primary moiety responsible for the efflux of Aβ from the brain to the blood across the blood–brain barrier. Impaired brain-to-blood transport of Aβ by LRP1 has been hypothesized to contribute to increased levels of Aβ in AD brain. The cause of LRP1 dysfunction is unknown, but we have hypothesized that Aβ oxidizes LRP1, thus damaging its own transporter. Consistent with this notion, we report in this study a significant increase in the levels of the lipid peroxidation product 4-hydroxy-2-nonenal bound to transmembrane LRP1 in AD hippocampus. In contrast, the levels of LRP1-resident 3-nitrotyrosine did not show a significant increase in AD hippocampus compared to age-matched controls. Based on this study, we propose that Aβ impairs its own efflux from the brain by oxidation of its transporter LRP1, leading to increased Aβ deposition in brain, thereby contributing to subsequent cognitive impairment in AD.